Oxadiazole and their Synthetic Analogues: An Updated Review: Oxadiazole and their Synthetic Analogues: An Updated Review - Yadav, Sonia (International Journal of Pharmaceutical & Biological Archive, 2018)
Oxadiazole and its tested derivatives with diverse pharmacological activities come under an important class of compounds in new drug development. The novel oxadiazole derivatives synthesized and investigated for their chemical and biological behavior has showed more importance in the recent era. In the previous studies, it was found that synthetic modification of oxadiazole ring has higher efficacy with improved potency and lesser toxicity. The present review provides an overview on the work done so far on oxadiazole and its biological activities (2008-2018).